Functional and perceptive differences between conventional and advanced ankle foot orthoses in community ambulators post-limb trauma: the injuries managed with advanced bracing of the lower extremity (IM ABLE) study - Highsmith, M. Jason; Miro, Rebecca M.; Kartel, Michael; Ramrattan, Anita; Courtade, Angela; Heckman, Jeffrey T.; Phillips, Samuel L.; Wurdeman, Shane R.; DiBello, Thomas V.; England, Dwiesha L.; Stevens, Phillip M.; Campbell, James H.; et al. (Frontiers in Rehabilitation Sciences, 2024)
Many military Service Members as well as civilians suffer lower extremity trauma. There have been recent advancements in lower limb bracing technology, but it is still unclear whether these newer advanced braces improve comfort and function compared to more conventional bracing options. The IDEO (Intrepid Dynamic Exoskeletal Orthosis), one type of "advanced" orthosis was developed to assist in maintaining high functional performance in patients that have experienced high energy lower extremity trauma and limb salvage surgeries. A cross-sector multi-site initiative was completed to study the efficacy of advanced ankle foot orthosis (AFO) for lower limb trauma and injury compared to a conventional AFO. Following fitting, training, and accommodation, subjects were assessed in each AFO system for mobility, self-reported function, safety and pain and finally, for preference. Subjects preferred the advanced over the conventional AFO and the mobility and exertion perception improved with the advanced AFO with no difference in pain or overall health status scores. An advanced AFO is an option for trauma affecting the lower limb. Long term studies are suggested to better understand the accommodation and learning process of using an advanced AFO.